Prognostic implications of MRI-detected lateral nodal disease and extramural vascular invasion in rectal cancer. Issue 13 (6th August 2018) - Schaap, D P; Ogura, A; Nederend, J; Maas, M; Cnossen, J S; Creemers, G J; van Lijnschoten, I; Nieuwenhuijzen, G A P; Rutten, H J T; Kusters, M
Abstract: Background: Lateral nodal disease in rectal cancer remains a subject of debate and is treated differently in the East and the West. The predictive value of lateral lymph node and MRI-detected extramural vascular invasion (mrEMVI) features on oncological outcomes was assessed in this study. Methods: In this retrospective cohort study, data on patients with cT3–4 rectal cancer within 8 cm from the anal verge were considered over a 5-year period (2009–2013). Lateral lymph node size, malignant features and mrEMVI features were evaluated and related to oncological outcomes. Results: In total, 192 patients were studied, of whom 30 (15·6 per cent) underwent short-course radiotherapy and 145 (75·5 per cent) received chemoradiotherapy. A lateral lymph node short-axis size of 10 mm or more was associated with a significantly higher 5-year lateral/presacral local recurrence rate of 37 per cent, compared with 7·7 per cent in nodes smaller than 10 mm ( P = 0·041). Enlarged nodes did not result in a higher 5-year rate of distant metastasis (23 per cent versus 27·7 per cent in nodes smaller than 10 mm; P = 0·563). However, mrEMVI positivity was related to more metastatic disease (5-year rate 43 versus 26·3 per cent in the mrEMVI-negative group; P = 0·014), but not with increased lateral/presacral recurrence. mrEMVI occurred in 46·6 per cent of patients with nodes smaller than 10 mm, compared with 29 per cent in patients with nodes of 10 mm or larger ( P = 0·267 ) . Conclusion: Although lateral nodal disease is more a local problem, mrEMVI mainly predicts distant recurrence. The results of this study showed an unacceptably high local recurrence rate in patients with a short axis of 10 mm or more, despite neoadjuvant (chemo)radiotherapy. Abstract : Defines recurrence risk